The relation between cigarette taxes and older adult smoking in Zhejiang and Gansu: what happened following the 2009 Chinese Tax adjustments? - Qing Wang (Komiyama Printing Co. Ltd, 2017)
Abstract Background In May 2009, the Chinese government raised cigarette excise tax rates and adjusted standards for Grade A cigarettes and Grade B cigarettes. The present study aimed to examine the effects of the tax adjustments in 2009 on smoking behaviors and health outcomes among smokers aged above 45. Methods Data from the 2008 and 2012 China Health and Retirement Longitudinal Study of Zhejiang and Gansu provinces were used to estimate the influence of tax increase on the number of cigarettes smoked daily and health capital. The sample included 706 smokers who were 45 years old and older at the time of data collection in 2008. The sample group was surveyed again in 2012. The final sample size was 1366. Logit model was applied. Results Cigarette tax adjustment in 2009 resulted in the decrease in the likelihood of smoking 0-10 cigarettes per day by 1.06%; the increase in the likelihood of those smoking 11-20 cigarettes per day by 0.44%; and, those smoking 20 cigarettes or more by 0.63%; the decrease in the likelihood of good health by 0.47%; the increase in the prevalence of chronic disease by 1.34%. Conclusions The smoke tax adjustment in 2009 worsened individual unhealthy smoking behaviors and health outcomes. The proposed cigarette tax levied at the retail level can reduce the State Tobacco Monopoly Administration's control overall and each price and increase the influence of the market on cigarette consumption in China.